Pengaruh Faktor-faktor Fundamental (Current Ratio, Return on Asset, Return on Equity, Total Asset Turn Over, Debt to Equity Ratio, dan Asset Growth) terhadap Beta Saham Telekomunikasi di Bursa Efek Indonesia Tahun 2019-2021 - Atti Rasnawati; Muryati Muryati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study raises the issue of Fundamental Factors, namely Current Ratio, Return On Assets, Return On Equity, Total Asset Turn Over, Debt To Equity Ratio, and Asset Growth have an influence or not on Beta Stocks. The purpose of this study is to determine how much the size of the company's ability to complete each fundamental ratio and how much influence the fundamental factors have on the stock beta of the telecommunications company. The results of this study indicate that the ability of telecommunications companies to have an average Current Ratio < standard deviation which means that the distribution of Current Ratio values is not good, while Return On Assets, Return On Equity, Total Assets Turn Over, Debt To Equity Ratio, and Asset Growth are in good condition. good. For statistical t-test, stock beta has no partial effect on Current Ratio, Return On Assets, Return On Equity, Total Assets Turn Over, Debt To Equity Ratio and Asset Growth. For testing F statistics that Current Ratio, Return On Assets, Return On Equity, Total Assets Turn Over, Debt To Equity Ratio, and Asset Growth do not have a simultaneous effect on the Beta Stocks.